Mengenal Allah melalui Pewahyuan - Anwar Three Millenium Waruwu (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
Revelation is God's effort, which can be seen from the words and what He does to reveal Himself and His will to humans. In that way, He revealed Himself to man, and man could know Him. However, human knowledge of God is minimal because of the lack of human awareness about revelation. This research examines